Underutilization of Supplemental Magnetic Resonance Imaging Screening Among Patients at High Breast Cancer Risk - Miles, Randy (J Womens Health (Larchmt), 2018)
Background: Women at high lifetime breast cancer risk may benefit from supplemental breast magnetic resonance imaging (MRI) screening, in addition to routine mammography screening for earlier cancer detection. Materials and Methods: We performed a cross-sectional study of 422,406 women undergoing routine mammography screening across 86 Breast Cancer Surveillance Consortium (BCSC) facilities during calendar year 2012. We determined availability and use of on-site screening breast MRI services based on woman-level characteristics, including >20% lifetime absolute risk using the National Cancer Institute risk assessment tool. Multivariate analyses were performed to determine sociodemographic characteristics associated with on-site screening MRI use. Results: Overall, 43.9% (2403/5468) of women at high lifetime risk attended a facility with on-site breast MRI screening availability. However, only 6.6% (158/2403) of high-risk women obtained breast MRI screening within a 2-year window of their screening mammogram. Patient factors associated with on-site MRI screening use included younger (<40 years) age (odds ratio [OR] = 2.39, 95% confidence interval [CI]: 1.34–4.21), family history (OR = 1.72, 95% CI: 1.13–2.63), prior breast biopsy (OR = 2.09, 95% CI: 1.22–3.58), and postsecondary education (OR = 2.22, 95% CI: 1.04–4.74). Conclusions: While nearly half of women at high lifetime breast cancer risk undergo routine screening mammography at a facility with on-site breast MRI availability, supplemental breast MRI remains widely underutilized among those who may benefit from earlier cancer detection. Future studies should evaluate whether other enabling factors such as formal risk assessment and patient awareness of high lifetime breast cancer risk can mitigate the underutilization of supplemental screening breast MRI.